THE VIEWS OF PROSPECTIVE STUDENTS NEW STUDENT PATHWAY SNBT 2024 THROUGH MEDIA MONITORING VOCATIONAL UNIVERSITY INDONESIA - Siagian, Beatrix (Jurnal Vokasi Indonesia, 2025)
This study aims to analyze the perceptions and views of prospective new students on the selection of SNBT admissions in 2024 in the UI Vocational Education Program. All information contained is obtained through social media monitoring carried out in the January-July 2024 period, with social media coverage namely Instagram, X, Tiktok, and Youtube. This research produces the main perceptions, main topics, and sentiment analysis of all study programs in UI Vocational Education and sentiments related to several specific topic categories. Based on the results of the analysis, it was found that conversations regarding the selection of SNBT admissions in 2024 at UI Vocational School dominated discussions on social media with a portion of 92.2%, compared to Gadjah Mada University (UGM) Vocational School which only reached 7.8%. The top topics are dominated by discussions covering tuition fees (UKT), capacity, and prospective new students' perceptions of SNBT selection. Sentiment is dominated by neutral with a total of 78%. Sentiments were positive regarding the reputation of UI Vocational School, but also accompanied by negative sentiments regarding tuition fees that are considered expensive and limited capacity. When viewed in terms of engagement, Instagram social media is the platform that shows the highest interaction, while Twitter and YouTube show lower engagement.